1996
DOI: 10.2739/kurumemedj.43.73
|View full text |Cite
|
Sign up to set email alerts
|

A Patient with Chronic Hepatitis C and a History of Abuse of Analeptic Drugs, Who Showed Hallucination and Delusion with Interferon Administration.

Abstract: Summary: We experienced a case of chronic hepatitis type C accompanied with hallucination and delusion induced by interferon (IFN) therapy positive. The case was a 47-year-old male, whose laboratory data showed positive for antiHepatitis C Virus (HCV) and elevated transa ninase level. He was treated with 6 MU/day of natural-type IFN-a (HLBI). Sleeplessness and delusions of persecution developed about 2 months after the start of IFN therapy. The interview of the psychiatrist disclosed that the patient had a his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Three cases of psychotic episodes have been described after 4–12 weeks of IFN-α treatment [62]. Manic and delirious episodes, with persecution and complex thought disorder, have also been described after several weeks or months of IFN-α therapy [33,51,62,64,66].…”
Section: Resultsmentioning
confidence: 99%
“…Three cases of psychotic episodes have been described after 4–12 weeks of IFN-α treatment [62]. Manic and delirious episodes, with persecution and complex thought disorder, have also been described after several weeks or months of IFN-α therapy [33,51,62,64,66].…”
Section: Resultsmentioning
confidence: 99%
“…In the second patient, IFN therapy was associated with emergence of PTSD symptoms in a patient with a history of trauma. In patients with a history of substance abuse disorder, flashbacks have been reported following treatment with natural IFN alfa (77).…”
Section: Isolated Ifn-induced Psychiatric Symptomsmentioning
confidence: 99%
“…The high rate of psychiatric comorbidity with increased risk of severe psychiatric side-effects might further complicate IFN-α treatment further (Renault and Hoofnagle, 1989;Muraoka et al, 1996). There are a few case reports of psychotic episodes in drug users during IFN-α treatment (Renault et al, 1987;McDonald et al, 1987;Hendrik, 1994;Muraoka et al, 1996) and these have been interpreted as flash-back psychosis, or delirium, due to previous drug abuse.…”
Section: Introductionmentioning
confidence: 95%
“…There are a few case reports of psychotic episodes in drug users during IFN-α treatment (Renault et al, 1987;McDonald et al, 1987;Hendrik, 1994;Muraoka et al, 1996) and these have been interpreted as flash-back psychosis, or delirium, due to previous drug abuse. However, a recent study has shown that patients with hepatitis C and mood or anxiety disorders were not more likely to develop psychiatric side-effects compared to normal controls when receiving IFN-α treatment, although these patients are thought of as contraindicated for IFN-α treatment (Pariente et al, 1999).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation